Synthesis of Methyl Axenoside and Methyl 3-epi-Axenoside via Ate-Mediated Allylic Substitution (AMAS) - Ondrusek, Brian A.; McQuade, D. Tyler (Synlett, 2014)
An ate-mediated allylic substitution (AMAS) of vinylboronates is utilized in the divergent syntheses of the sugars methyl axenoside and methyl 3-epi-axenoside. Other key steps of the synthesis involve the dihydroxylation of the resulting allylic alcohol and selective oxidation of the resultant diol. Benefits of this methodology are also discussed.
Keywords: asymmetric synthesis; boron; homogeneous catalysis; natural products; total synthesis